Trends on enzyme immobilization researches based on bibliometric analysis - Gonçalves, Maria Carolina Pereira; Kieckbusch, Theo Guenter; Perna, Rafael Firmani; Fujimoto, Jaqueline Tomiê; Morales, Sergio Andres Villalba; Romanelli, João Paulo (Process biochemistry (1991), 2019)
•China and USA have been accumulating the most publications in the last 27 years.•Spanish authors were the ones that most contributed in this domain.•Reduced collaborative networks restrict search focuses.•Keywords analysis offered relevant information on the research trends and gaps. In this survey, a bibliometric analysis of the global scientific production on enzyme immobilization researches was developed using Web of Science© database. The time-span comprised the period from 1991 to 2017. A total of 9636 documents related to the subject were retrieved and analyzed according to seven main aspects: publication years, journals, countries, authors, organizations, keywords, and Web of Science categories. The results indicated that the countries with the highest number of publications were China and the United States. The most expressive international collaborative networks were evidenced between Brazil and Spain and between the USA and China. Additionally, the Spanish researchers were the ones that contributed most to this domain, while the Consejo Superior de Investigaciones Científicas and the Chinese Academy of Sciences were the most emblematic organizations. Finally, the analysis of keywords revealed that biosensor, lipase and glucose oxidase were the most cited terms among all publications, and also indicated the existence of a possible knowledge gap involving the terms Escherichia coli, Candida rugosa lipase and cytochrome-c in the context of enzyme immobilization. This study was efficient to evaluate the trends of the body of literature on enzyme immobilization research, subsidizing future decision-making in this field of science.